B-type natriuretic peptide is a determinant of the nocturnal increase in blood pressure independently of arterial hypertrophy and hypoxia. Issue 12 (December 2016) - Tabara, Yasuharu; Igase, Michiya; Miki, Tetsuro; Ohyagi, Yasumasa; Matsuda, Fumihiko; Kohara, Katsuhiko; ,
Abstract : Objective: Loss of the nocturnal blood pressure (BP) drop is a risk factor for cardiovascular outcomes. However, clinical parameters that predispose to changes in nocturnal BP are currently uncertain. Given the possible involvement of salt sensitivity in nocturnal BP levels, we investigated a hypothesized association between plasma B-type natriuretic peptide (BNP) levels – a marker of body fluid retention – and nocturnal BP in a general population. Methods: Study participants were 1020 general individuals. Participants were divided into four groups (riser, nondipper, dipper, and extreme dipper) by their percentage changes in nocturnal SBP measured using an ambulatory BP monitor. Results: Plasma BNP levels were positively associated with circadian BP change ( β  = 0.162, P  < 0.001) independently of carotid hypertrophy ( β  = 0.133, P  < 0.001), and awake heart rate ( β  = −0.102, P  = 0.001) and SBP ( β  = −0.246, P  < 0.001). Risers showed 1.6 times higher BNP levels than dippers, whereas oxygen desaturation during sleep was frequently observed in nondippers. Results of multinomial logistic regression analysis indicated that BNP level was a significant determinant for the riser pattern [odds ratio (OR) 1.27 (BNP 10 pg/ml), P  < 0.001], whereas oxygen desaturation was specifically associated with the nondipping pattern (OR 1.04, P  = 0.001). When participants were subdivided by BNP level, risers were more frequent in the high BNP subgroup (19.5%) than in the low BNP subgroup (6.7%) (OR 3.39, P  < 0.001). Conclusion: A slight increase in plasma BNP level was independently associated with rising nocturnal BP. Our results may help to understand the pathophysiology of circadian BP variation, and be a clue to identify individuals who require careful BP monitoring.